FPGA Implementation of a Chaos-based Stream Cipher and Evaluation of its Performances. Issue 1 (2020) - Dridi, Fethi; Atamech, Carinelle; Assad, Safwan El; Youssef, Wajih Elhadj; Machhout, Mohsen
No abstract available